The Informational Role of Implied Volatility : Examining the relation between implied volatility and S&P 100 returns around FOMC announcements - Auvinen, Iiro (My University, 2020)
Volatility has been a widely discussed subject in financial research and many papers consider it synonymous with the risk of an investment. However, further research has revealed that besides exhibiting the level of risk, volatility has more wide-ranging implications. Empirical evidence indicates that the forward-looking measures of volatility may have informational value over future equity returns. This thesis studies the relation between implied volatility and equity returns around FOMC interest rate announcements. The main purpose of this thesis is to examine whether FOMC announcements increase the level of information that implied volatility contains about future stock returns. The research framework is motivated by the findings of Du, Fung & Loveland (2018) about the increased return predictability in the banking sector. This thesis contributes to the existing literature by examining the information content of implied volatility in a market-wide context. By using daily observations from 1995 to 2008, multivariate regressions are run in an attempt to explain stock returns by lagged changes in implied volatility and binary variables that identify FOMC announcement days. The possible impact of FOMC announcements on return predictability associated with implied volatility is studied by augmenting the model with an interaction variable. For further examination, daily changes in implied volatility are divided into quartiles so that it is possible to examine whether the magnitude of change in implied volatility impacts return predictability. Additionally, the sample period is divided into two subsamples so that any timely differences can be perceived. Finally, similar regressions are applied to the days surrounding the actual announcement days. The results of this thesis suggest that stock returns are positively associated with not only the lagged changes in implied volatility but also FOMC announcements in general. These findings are consistent with the previous studies. Regarding the hypothesized increase in return predictability, significant results are attained for certain subsamples and days following the FOMC announcements. Even though these results do not directly suggest that the findings of Du et al. (2018) apply in a market-wide context, this thesis provides qualified evidence that FOMC announcements have a positive influence on the predicting power of implied volatility. Therefore, this thesis motivates to examine the information content of implied volatility in future research as well.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance